2016
DOI: 10.1111/nph.13893
|View full text |Cite
|
Sign up to set email alerts
|

Root‐knot nematodes induce pattern‐triggered immunity in Arabidopsis thaliana roots

Abstract: SummaryRoot-knot nematodes (RKNs; Meloidogyne spp.) are plant parasites with a broad host range causing great losses worldwide. To parasitize their hosts, RKNs establish feeding sites in roots known as giant cells. The majority of work studying plant-RKN interactions in susceptible hosts addresses establishment of the giant cells and there is limited information on the early defense responses.Here we characterized early defense or pattern-triggered immunity (PTI) against RKNs in Arabidopsis thaliana. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 98 publications
(152 reference statements)
2
87
0
Order By: Relevance
“…Mi‐CRT and Misp12 from M. incognita and MjTTL5 from M. javanica are effectors in PPNs that suppress PTI . The study of plant defenses against nematodes has concentrated on disease resistance proteins and effector‐triggered immunity (ETI) . In direct and indirect host recognition of pathogen effectors, local and systemic changes in gene expression are mediated largely by the MYB and WRKY transcription factors families .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mi‐CRT and Misp12 from M. incognita and MjTTL5 from M. javanica are effectors in PPNs that suppress PTI . The study of plant defenses against nematodes has concentrated on disease resistance proteins and effector‐triggered immunity (ETI) . In direct and indirect host recognition of pathogen effectors, local and systemic changes in gene expression are mediated largely by the MYB and WRKY transcription factors families .…”
Section: Discussionmentioning
confidence: 99%
“…In direct and indirect host recognition of pathogen effectors, local and systemic changes in gene expression are mediated largely by the MYB and WRKY transcription factors families . It has been reported that AtWRKY23 is expressed during the early stages of feeding site establishment of PPNs, and WRKY11 and WRKY17 are positive regulators of RKN defense . Overexpression of WRKY41 showed enhanced resistance to pathogens in A. thaliana , inducing expression of the PR5 gene, but suppression of the MeJA‐induced PDF1.2 gene .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camalexin is a well-known antimicrobial compound. An Arabidopsis mutant line with impaired camalexin synthesis supported significantly more gall production than the wild type 56 . In the cell signaling category, phosphoinositide synthesis and degradation were modulated similarly between Gregory and Tifguard upon nematode invasion.…”
Section: Discussionmentioning
confidence: 96%
“…Together, these data suggest that receptor‐mediated perception of Peps triggers RBOHD‐dependent ROS production via a BAK1/BIK1 phosphorylation cascade. Previous studies have shown that PTI against RKNs in Arabidopsis is compromised in mutants with impairments in BAK1 , BIK1 or NADPH oxidase genes ( RBOHD/F ) (Teixeira et al ., ). Comparison of transcript profiles induced by SCN in resistant versus susceptible soybean cultivars also indicates that BIK1 and RBOHD induction correlate with cyst nematode resistance (Matsye et al ., ; Wan et al ., ).…”
Section: Introductionmentioning
confidence: 97%